A novel de novo dominant mutation in ISCU associated with mitochondrial myopathy. Issue 12 (27th October 2017) - Legati, Andrea; Reyes, Aurelio; Ceccatelli Berti, Camilla; Stehling, Oliver; Marchet, Silvia; Lamperti, Costanza; Ferrari, Alberto; Robinson, Alan J; Mühlenhoff, Ulrich; Lill, Roland; Zeviani, Massimo; Goffrini, Paola; et al.
Abstract : Background: Hereditary myopathy with lactic acidosis and myopathy with deficiency of succinate dehydrogenase and aconitase are variants of a recessive disorder characterised by childhood-onset early fatigue, dyspnoea and palpitations on trivial exercise. The disease is non-progressive, but life-threatening episodes of widespread weakness, metabolic acidosis and rhabdomyolysis may occur. So far, this disease has been molecularly defined only in Swedish patients, all homozygous for a deep intronic splicing affecting mutation in ISCU encoding a scaffold protein for the assembly of iron–sulfur (Fe-S) clusters. A single Scandinavian family was identified with a different mutation, a missense change in compound heterozygosity with the common intronic mutation. The aim of the study was to identify the genetic defect in our proband. Methods: A next-generation sequencing (NGS) approach was carried out on an Italian male who presented in childhood with ptosis, severe muscle weakness and exercise intolerance. His disease was slowly progressive, with partial recovery between episodes. Patient's specimens and yeast models were investigated. Results: Histochemical and biochemical analyses on muscle biopsy showed multiple defects affecting mitochondrial respiratory chain complexes. We identified a single heterozygous mutation p.Gly96Val in ISCU, which was absent in DNA from his parents indicating a possible de novo dominant effect in the patient. Patient fibroblasts showed normal levels of ISCU protein and a few variably affected Fe-S cluster-dependent enzymes. Yeast studies confirmed both pathogenicity and dominance of the identified missense mutation. Conclusion: We describe the first heterozygous dominant mutation in ISCU which results in a phenotype reminiscent of the recessive disease previously reported.